Assessing periodontal disease severity at the age of 17-45 years patients using panoramic radiograph - Barunawaty Yunus; Diazty Ningsih Tandililing (Makassar Dental Journal, 2020)
Introduction: Panoramic radiography is one type of extra oral application of X-rays. Objective: To determine the severity of periodontal disease at 17-45 yearspatients using panoramic radiograph at Hasanuddin University Dental Hospital. Method: Observational descriptive study using cross sectional study got all panoramic radiograph archive from June 2018 to June 2019, and presents in tables. Result: There was no significant relationship between age and the severity of periodontal disease, but there was a significant correlation between sex and the severity of attachment loss in second incisors. Conclusion: It was concluded that the prevalence of periodontal disease was highest on women and most vulnerable at the age of 27-36 years. That there was no significant relationship between age and sex in the severity of periodontal disease.